2011
DOI: 10.3892/or.2011.1378
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Nampt in gastric cancer and chemopotentiating effects of the Nampt inhibitor FK866 in combination with fluorouracil

Abstract: Abstract. Nicotinamide phosphoribosyltransferase (Nampt), an enzyme involved in the NAD + salvage pathway, is overexpressed and important in the carcinogenesis in several types of cancers. The expression of Nampt and its role in gastric cancer remain largely unknown. In this study, using real-time PCR and Western blotting we found that Nampt was overexpressed at the mRNA and protein levels, respectively, in established gastric cancer cells and human gastric cancer tissues. The specific Nampt inhibitor FK866 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…NAMPT has been found to be overexpressed in several types of tumors and its expression is associated to tumor progression (Bi et al, 2011; Hasmann and Schemainda, 2003; Van Beijnum et al, 2002; Wang et al, 2011). Consequently, several studies showed that the NAD + depletion triggered by the down-regulation of NAMPT activity can reduce tumor cell growth and sensitize cells to chemotoxic agents (Bi et al, 2011; Hasmann and Schemainda, 2003; Wang et al, 2011; Watson et al, 2009). One must keep in mind that in most cancer cells, PARPs are activated due to DNA damage and genome instability, leading to NAD + depletion in cancer cells (Garten et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…NAMPT has been found to be overexpressed in several types of tumors and its expression is associated to tumor progression (Bi et al, 2011; Hasmann and Schemainda, 2003; Van Beijnum et al, 2002; Wang et al, 2011). Consequently, several studies showed that the NAD + depletion triggered by the down-regulation of NAMPT activity can reduce tumor cell growth and sensitize cells to chemotoxic agents (Bi et al, 2011; Hasmann and Schemainda, 2003; Wang et al, 2011; Watson et al, 2009). One must keep in mind that in most cancer cells, PARPs are activated due to DNA damage and genome instability, leading to NAD + depletion in cancer cells (Garten et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, NAMPT has a crucial role in cancer cell metabolism [7]. NAMPT expression was found to be increased in numerous types of tumors, including colorectal cancer [8], breast cancer [9], gastric cancer [10], ovarian cancer [11], prostate cancer [12]. In these tumors, inhibition of NAMPT had a profound antitumor effect [812].…”
Section: Introductionmentioning
confidence: 99%
“…Higher visfatin levels in breast cancer are correlated with overall survival and disease-free survival [8]. Literatures also reported that visfatin overexpression can predict poor response of the patients to doxorubicin [9] or fluorouracil [10] based chemotherapy. Visfatin is closely associated with the pathogenesis of colon cancer, therefore it is considered as a novel and promising biomarker of CRC [11].…”
Section: Introductionmentioning
confidence: 99%